(untitled) (Nordic Journal of African Studies, 2005)
Morphological parsers are typically developed for languages without contrastive tonal systems. Ha, a typical Bantu language of Western Tanzania, proposes a challenge to these parses with both lexical and grammatical pitch-accent that would, in order to describe the tonal phenomena, seem to require an approach with a separate level for the tones. However, since the Two-Level Morphology (Koskenniemi 1983) has proven successful with another Bantu language, Swahili (Hurskainen 1999), it is worth testing its possibilities with the tonally more challenging Bantu languages. The purpose of this paper is to show that morphological parsing of a fairly complex pitch-accent system is indeed possible with the Two-Level approach, but the solutions do not always describe the actual tonal system of the language.